2016
DOI: 10.1139/tcsme-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Performance Degradation Assessment by Orthogonal Local Preserving Projection and Continuous Hidden Markov Model

Abstract: Bearing is the key component in rotating machine. It is important to assess the performance degradation degree of bearings for making proactive maintenance and realizing near-zero downtime. A methodology based on orthogonal local preserving projection (OLPP) and continuous hidden Markov model (CHMM) is introduced in bearing performance degradation assessment. Firstly, the time domain, frequency domain and time-frequency domain features are extracted from the vibration signals. Then, the multi-dimensional featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To establish the index with an obvious trend, Li et al [225] proposed the negative log likelihood probability based on the two-dimensional HMM as the bearing performance degradation index, showing the sensitivity to weak defects. Liu et al [226] proposed a bearing DA method based on orthogonal local preserving projection (OLPP) and continuous HMM. The continuous HMM was used to train the data after dimension reduction by OLPP, and then the performance could be evaluated quantitatively by calculating the logarithmic likelihood of the data.…”
Section: Traditional Ml-based Methodsmentioning
confidence: 99%
“…To establish the index with an obvious trend, Li et al [225] proposed the negative log likelihood probability based on the two-dimensional HMM as the bearing performance degradation index, showing the sensitivity to weak defects. Liu et al [226] proposed a bearing DA method based on orthogonal local preserving projection (OLPP) and continuous HMM. The continuous HMM was used to train the data after dimension reduction by OLPP, and then the performance could be evaluated quantitatively by calculating the logarithmic likelihood of the data.…”
Section: Traditional Ml-based Methodsmentioning
confidence: 99%
“…Wang et al [24] identified the running state of the spot welding machining process by HMM. Liu et al [25] proposed a bearing performance degradation evaluation method by orthogonal locally retained projection and continuous HMM. Zhou et al [26] proposed a fault diagnosis by a shift-invariant dictionary learning and HMM.…”
Section: Introductionmentioning
confidence: 99%